Union negotiation and wage inequality in Argentina: an empirical analysis of recent trends - Ronconi, Juan Pedro (2013)
In conjunction with the recovery of the Argentine economy between 2003 and 2011, income distribution improved considerably. Though it does not provide a quantitative assessment, the relevant literature points to the resurgence of union negotiation as central to this process. This paper provides an account of the evolution of intra-union and inter-union inequality in basic wage agreements signed during this period, and reveals considerable improvements in both. The second part of the paper studies the behavior of the Federación de Camioneros (Truckers’ Federation) and its role in wage negotiations during the same period.